2017
DOI: 10.3390/en10030334
|View full text |Cite
|
Sign up to set email alerts
|

Flame Structure and Chemiluminescence Emissions of Inverse Diffusion Flames under Sinusoidally Driven Plasma Discharges

Abstract: Reduction of nitric oxides (NO x ) in aircraft engines and in gas turbines by lean combustion is of great interest in the design of novel combustion systems. However, the stabilization of the flame under lean conditions is a main issue. In this context, the present work investigates the effects of sinusoidal dielectric barrier discharge (DBD) on a lean inverse diffusive methane/air flame in a Bunsen-type burner under different actuation conditions. The flame appearance was investigated with fixed methane loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Nowadays, plasma ignited combustion is one of the most prominent and leading technology due to its growing interest in the applications of aeronautical engines [1]. Plasma discharge has the potential to enhance the combustion and flame stability by three ways: thermal effect due to Joule heating, kinetic effect with production of ions, electrons, excited species and free radicals, and the last one via transport (low temperature oxidation and fuel decomposition) [2][3]. Concerning the chemistry modification induced by plasma discharges, kinetic processes occur when electron gained additional energy and collides with gas mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, plasma ignited combustion is one of the most prominent and leading technology due to its growing interest in the applications of aeronautical engines [1]. Plasma discharge has the potential to enhance the combustion and flame stability by three ways: thermal effect due to Joule heating, kinetic effect with production of ions, electrons, excited species and free radicals, and the last one via transport (low temperature oxidation and fuel decomposition) [2][3]. Concerning the chemistry modification induced by plasma discharges, kinetic processes occur when electron gained additional energy and collides with gas mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Mei et al [16] studied the effects of coflow velocity on flame shape and size by performing CFD calculation. Giorgi et al [17] observed the flame structure for an inverse diffusion combustion with a chemiluminescence emission method. Wang et al [18] examined the evolution of the flame length of a buoyant jet diffusion flame restricted by parallel sidewalls at reduced pressure; they pointed out that the flame length at decreased pressure is found to be slightly longer than that at normal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A novel technology that emerged as an alternative to fluidic actuators at the end of the 1990s and is suitable for use in gas flows is to use dielectric barrier discharge (DBD) plasma [64][65][66][67][68]. The DBD plasma actuators can induce steady or unsteady jets tangential to the surface on which they are mounted causing a net flux of momentum to the exterior flow somewhat similar to the synthetic jet.…”
Section: Afc Local Actuatorsmentioning
confidence: 99%